La Persona De Leo N. . The Person De Leo N - Vendemmiati, Alberto (Arcopinto, Gianluca ; Fornari, Andrea ; Vendemmiati, Alberto, 2005)
Duration: 01:26:00 Since 1982, Italian transsexuals have been able to have a sex change operation that is subsidised according to Section 164 of the law. Those eligible are also assisted in changing their sexual identity on paper. The condition is that they subject themselves to a complicated, lengthy and psychologically gruelling procedure. As a twelve-year-old boy, Nicola de Leo already knew she wanted to become a woman. Today, the now forty-year-old transsexual lives in Venice and has changed her name to Nicole. She has undergone hormone treatment and grown breasts, but she still lives inside the body of a middle-aged man, including a penis, a beard and a substantial Adam's apple. This is why Nicole is applying for a sex change through official channels. "I never thought it would be so hard. I thought making the decision was enough", she says. For five tense years, Nicole fights her emotional and physical struggle in the presence of director Alberto Vendemmiati's camera. Working as an actress, a seller of carnival masks and a prostitute, she finances her cosmetic treatment and looks forward to the subsidised sex change operation. Meanwhile, she turns for support to her elderly mother, who has a hard time accepting that her son will soon be a daughter.